Analysis of the Current Situation of Economic Development in Shandong Province from 2004 to 2021 - Wang, Mengdi (International Journal of Global Economics and Management, 2024)
As one of China’s major economic provinces, Shandong Province has experienced significant economic growth from 2004 to 2021, and its total GDP ranks among the top in the country. In 2021, Shandong’s GDP increased by 8.3% year-on-year, with the service sector contributing particularly prominently to GDP, accounting for 52.8% of GDP, while foreign trade also showed a rapid growth trend. Despite the challenges of unbalanced urban-rural development and the need to optimize the industrial structure, Shandong Province has laid a solid foundation for the sustained and healthy development of the economy by adjusting its industrial layout and actively expanding its opening up to the outside world. Since the beginning of the new century, especially in the period of rapid development of heavy chemical industry, Shandong Province has successfully grasped the development opportunity and vigorously developed heavy industries such as petrochemical and oil refining through an investment-driven strategy, further strengthening its important position in the national and global economy.